Market mechanisms in the eastern part of Indonesia of PTKI company - Kasiani, Kasiani; Sarjana, I Made; Sanjaya, I Gusti Ngurah; Kencanawati, Anak Agung Ayu Mirah; Marheni, Lily (YAYASAN MITRA PERSADA NUSANTARA, 2024)
The objectives of this research are to analyse (1) products marketed to Eastern Indonesia by PTKI company; (2) the form of organizational structure applied; (3) the market mechanism implemented; (4) tasks carried out by the leadership of the company in the area. Direct interviews with the leaders of the three regions, as well as secondary data collected through the company’s website. The analysis technique used is descriptive qualitative, namely a clear description of the market mechanism of the company in the Eastern Indonesia Region. The results of the research are (1) all the products marketed are non-food products such as skincare, sanitary napkins and detergent. (2) The company has a line organizational structure and has duties and responsibilities from superiors to subordinates. (3) The market mechanism implemented starts from looking at the population of provincial, district and sub-district areas and BPS. (4) The leadership undertakes tasks related to planning, emphasizing the importance of instilling values in consumers. This encourages them to use the company’s products, which are integrated into their lives due to their adequate quality and reasonable price. The policies under the previous leadership are largely similar to those under the new leadership, with the primary difference being in the leadership style.